TCAS and the Stable Matching Problem: Theory and Implementation - Faugchun, Pattanarat (Thai Journal of East Asian Studies, 2019)
This article presents a summarized history of the university central admission systems in Thailand, as well as some details of the newly adopted Thai university Central Admission System (TCAS). Some key results in matching theory regarding the college admission problem are also reviewed. The article tries to build a bridge between the theory and real-world phenomena by noticing that some main problems in TCAS are symptoms of unstable matching and possible strategic manipulation. It then suggests that the Gale-Shapley student-optimal mechanism, using the celebrated Deferred Acceptance Algorithm (DAA), should be employed to prevent instability and induce truthful revelation from every student.